PROTOTYPE OF THE INTERNET OF THINGS-BASED SWALLOW BUILDING MONITORING AND SECURITY SYSTEM - Didit Suprihanto; Happy Nugroho; Aji Ery Burhandenny; Arif Harjanto; Muhammad Akbar (Informatika, Universitas Jenderal Soedirman, 2023)
The Swallow nest production in a cultivation building have high commercial value. There are several factors that affect nest productivity such as light intensity, temperature and humidity conditions in the cultivation building. Better factors can be found in cultivation building that located far from residential area. However, this led to a risk of theft. Therefore, this study proposes a system that able to monitor the productivity factors and safety status of the building. System development uses a comparison method with black box testing. The system controller uses the Raspberry Pi B+ and the python programming language. Sensor Modules (GY-302, DHT-22, BME-280) are used to monitor light intensity, temperature and humidity. The security system uses sensor modules (LDR LM393, PIR HC-SR501 and SW-420) as flashlight, motion and vibration detectors. The black box testing result shows a good performance of the proposed system. The monitoring and security system can monitor the condition of swallow cultivation parameters and security status that can turn on alert alarms, send WhatsApp messages, store log data and send data to the website periodically according to the level of conditions that occur.